Desymmetrization of Viologen Anolytes Empowering Energy Dense, Ultra Stable Flow Batteries toward Long‐Duration Energy Storage. Issue 41 (11th September 2022) - Hu, Maowei; Wu, Wenda; Luo, Jian; Liu, T. Leo
Abstract: Aqueous organic redox flow batteries (AORFBs) have been recognized as a promising technology for large‐scale, long‐duration energy storage of renewables (e.g., solar and wind) by overcoming their intermittence and fluctuation. However, simultaneous demonstration of high energy densities and stable cycling are still challenging for AORFBs. Herein, asymmetrically substituted sulfonate viologen molecular designs, e.g. (1‐[3‐sulfonatopropyl]‐1′‐[4‐sulfonatobutane]‐4, 4′‐bipyridinium (3, 4‐S2 V), as capacity dense, chemically stable anolytes for cation exchange AORFBs are presented. The robust cycling performance of 3, 4‐S2 V is confirmed using half‐cell and full‐cell flow battery studies at pH neutral conditions. The 3, 4‐S2 V based AORFB is demonstrated with a discharge capacity of 23.2 Ah L −1 for 1700 cycles or 100 days without observing chemical degradation. Furthermore, a 3, 4‐S2 V/(NH4 )4 [Fe(CN)6 ] AORFB with a discharge capacity of 259.9 mAh is demonstrated for 50 days of authentic energy storage for the first time with a total capacity retention of 97.77% or a temporal capacity retention rate of 99.955% per day, representing the most stable, longest cycled AORFB to date. Abstract : An asymmetrically substituted sulfonate viologen molecular design, i.e. (1‐[3‐sulfonatopropyl]‐1′‐[4‐sulfonatobutane]‐4, 4′‐bipyridinium (3, 4‐S2 V), is developed as a capacity dense, chemically stable anolyte for aqueous organic redox flow batteries with a demonstrated discharge capacity of 23.3 Ah L ‐1 for 1700 cycles or 100 days.